2016
DOI: 10.1371/journal.pone.0166907
|View full text |Cite
|
Sign up to set email alerts
|

The Florida Harvester Ant, Pogonomyrmex badius, Relies on Germination to Consume Large Seeds

Abstract: The Florida harvester ant, Pogonomyrmex badius, is one of many ant species and genera that stores large numbers of seeds in damp, underground chambers for later consumption. A comparison of the sizes of seeds recovered from storage chambers with those of seed husks discarded following consumption revealed that the used seeds are far smaller than stored seeds. This difference in use-rate was confirmed in field and laboratory colonies by offering marked seeds of various sizes and monitoring the appearance of siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Four size classes of the 2014 seeds were used in a series of experiments on the consumption of germinating and non-germinating seeds. The results of these studies can be found in Tschinkel and Kwapich [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four size classes of the 2014 seeds were used in a series of experiments on the consumption of germinating and non-germinating seeds. The results of these studies can be found in Tschinkel and Kwapich [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although early observers sometimes noted germinating seeds in the nests of harvesting ants, the possibility that the ants might actually require some seeds to germinate in order to be able to eat them was never carefully investigated until the recent work of Tschinkel and Kwapich [ 21 ]. Through experiments and observations, Tschinkel and Kwapich [ 21 ] showed that P .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cereal grains like Millet, Wheat, Sorghum and Rice are major staple foods and raw materials in bakeries and brewing industries which have been reported to be ravaged by the activities of harvester ants (Nicola et al, 2013). As a field and store pest, the harvester ant causes extensive damage and losses by foraging on sown seeds, sometimes feeding on germinated crops and also climbing some plants to harvest matured seeds/grains (Heathwole, 1996;Tschinkel and Kwapich, 2016). They also reduce plant stands by denudation of cultivated lands as they destroy the plants around the entrance to their nest leading to bare patches in the fields measuring several square metres.…”
Section: Introductionmentioning
confidence: 99%